Copolycarbonate resin as well as preparation method and application thereof

By controlling the concentration of monomer batching liquid and polymerization reaction conditions, copolycarbonate resin is formed, which solves the problems of limited production capacity and high dielectric constant of polycarbonate resin, improves production efficiency and mechanical properties, and is suitable for high-speed electronic components.

CN119192554AActive Publication Date: 2024-12-27WANHUA CHEM GRP CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411341162.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-27
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The existing polycarbonate resins are difficult to increase the batching concentration at high concentrations, which limits production capacity, and have a relatively large dielectric constant, so they are not suitable for high-speed electronic components.

Method used

By controlling the concentration of the monomer batch liquid in the structure of formula (I), using an inert gas environment and an organic solvent, the monomer batch liquid, alkali liquid and phosgene are passed through to polymerize, forming a copolycarbonate resin, and increasing the tensile modulus of the resin and flexural modulus while reducing its relative dielectric constant.

Benefits of technology

The production efficiency of copolycarbonate resin is improved, the tensile modulus and flexural modulus are improved, and the dielectric constant is reduced, making it suitable for high-speed electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005059734510000021
    Figure BDA0005059734510000021
  • Figure BDA0005059734510000041
    Figure BDA0005059734510000041
  • Figure BDA0005059734510000091
    Figure BDA0005059734510000091
Patent Text Reader

Abstract

The invention provides copolycarbonate resin as well as a preparation method and application thereof. The copolycarbonate resin is prepared from comonomers with structures as shown in a formula (I) and a formula (II) through a phosgene interfacial polycondensation method, and the concentration of the monomer ingredient liquid with the structure as shown in the formula (I) is controlled, so that the relative dielectric constant of the copolycarbonate resin can be reduced, and the production efficiency, tensile modulus and flexural modulus of the resin can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polycarbonate, and in particular to a copolycarbonate resin and a preparation method and application thereof. Background Art

[0002] Polycarbonate resin is widely used as an engineering plastic with excellent transparency, impact resistance, etc. At the same time, as a composition, it is composed of polycarbonate components of different molecular weights. At present, phosgene-based polycarbonate is mainly prepared by interfacial polycondensation reaction using bisphenol A (BPA) and phosgene as raw materials. On the one hand, due to the particularity of the BPA raw material-it will precipitate in the form of hydrates at high concentrations, so that the ingredient concentration of the raw material cannot be further increased, limiting the production capacity of polycarbonate resin; on the other hand, as a conventional polycarbonate, its relative dielectric constant is large and is not suitable for the field of high-speed electronic components. Therefore, it is necessary to provide a preparation method that can improve the production capacity of polycarbonate resin and reduce the dielectric constant of polycarbonate resin. Summary of the invention

[0003] In order to solve the problems existing in the prior art, the present invention provides a method for preparing a copolycarbonate resin. By controlling the concentration of the monomer formulation liquid of the formula (I), the relative dielectric constant of the copolycarbonate resin can be reduced, the tensile modulus and the flexural modulus of the resin can be increased, and the production efficiency of the copolycarbonate can also be improved.

[0004] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solution:

[0005] In a first aspect, the present invention provides a method for preparing a copolycarbonate resin, and the specific preparation method comprises the following steps:

[0006] 1. Prepare monomer formulation solutions of formula (I) and formula (II);

[0007] 2. In an inert gas environment, in the presence of an organic solvent and a capping agent, monomer formulation liquid, alkali solution and phosgene are introduced for preparation.

[0008] Specifically, in step 1, the monomer batching liquids can be separately batched and then mixed, or can be directly mixed and batched.

[0009] Specifically, the monomer formulation solution in step 1 contains alkali, water, deoxidizer, monomers of formula (I) and / or monomers of formula (II).

[0010] Specifically, the monomers of the structures of formula (I) and formula (II) are shown below.

[0011]

[0012] Among them, R 1 , R2 , R 3 , R 4 are independently selected from H, halogen, C1-C 10 alkyl (preferably C1-C3 alkyl), C5-C6 cycloalkyl, C6-C 10 Any of the aryl groups of 5 , R 6 , R 7 are independently selected from H, C1-C 10 Any one of an alkyl group (preferably a C1-C3 alkyl group).

[0013] In a preferred embodiment, the monomer of the structure of formula (I) is one or more of BPTMC, bisphenol Z, and 1,1'-bis(4-hydroxy-3-methylphenyl)cyclohexane, more preferably BPTMC.

[0014] Specifically, in the monomer formulation liquid corresponding to the structure of formula (I) in step 1, the concentration of the structure of formula (I) is 160 g / L to 346 g / L, and the pH value of the formulation liquid is 11 to 13.5.

[0015] In a more preferred embodiment of the present invention, in the monomer formulation liquid of the structure of formula (I), the concentration of the structure of formula (I) is 216 g / L to 325 g / L, preferably 292 g / L to 314 g / L; the pH value of the formulation liquid is 11.5 to 13.5, preferably 12 to 13.

[0016] Specifically, the concentration of the structure of formula (II) in the monomer formulation liquid corresponding to the structure of formula (II) in step 1 is 155 g / L to 175 g / L, preferably 165 g / L to 170 g / L; the pH value of the formulation liquid is 12 to 13.5, preferably 12.5 to 13.

[0017] When the monomer batching liquid is separately batched, the above-mentioned monomer batching liquid concentration refers to the concentration of the batching liquid when it is separately batched; when the monomer batching liquid is mixed, the above-mentioned monomer batching liquid concentration refers to the concentration of each monomer in the total mixed monomer batching liquid; the present invention prefers separate batching.

[0018] The inventor has found that in the production of general-purpose polycarbonate resin, since BPA (Formula II structure monomer) can be separated out at high concentration, it is impossible to further improve the concentration of the batching liquid, so that production efficiency cannot be improved. However, when carrying out the synthesis of copolycarbonate resin, it is found that the monomer of Formula I structure can be batched at high concentration, which can significantly improve production efficiency, but too high batching concentration will increase the dissolution time, increase the batching liquid viscosity, and is not conducive to improving production efficiency. In addition, due to the higher reactivity of the monomer of Formula I structure than BPA, and the larger molecular rigidity, when reacting at high concentration, it is conducive to forming the block structure of the monomer of Formula I structure and the monomer of Formula II structure, the tensile modulus and the flexural modulus of the resin can be improved, and the relative dielectric constant of the resin is reduced.

[0019] Specifically, the base in step 1 is an inorganic base, selected from any one of NaOH, KOH, LiOH, and CsOH, or a combination of at least two thereof; the amount of the base added is adjusted according to the required pH of the monomer formulation solution.

[0020] Specifically, the deoxidizer in step 1 is selected from sodium dithionite and / or potassium dithionite; preferably, the amount of the deoxidizer added is 0.1 to 0.3% of the total molar amount of the monomer of the structure of formula (I) and the monomer of the structure of formula (II);

[0021] Specifically, when the monomers are separately formulated, it is well known to those skilled in the art that the deoxidizer should be added to the monomer formulation solution separately to avoid yellowing due to oxidation of the monomers.

[0022] Specifically, the organic solvent in step 2 is selected from any one of dichloromethane, chloroform, tetrachloromethane, dichloroethane, toluene, and chlorobenzene, or a combination of at least two thereof.

[0023] In a preferred embodiment, in step 2, the molar ratio of the total amount of monomers of formula (I) participating in the polymerization reaction to the monomers of formula (II) is 1:99 to 99:1, preferably 10:90 to 70:30, and more preferably 30:70 to 40:60.

[0024] In a preferred embodiment, in step 2, the phosgene is added continuously, and the phosgene is continuously introduced during the reaction, and the total molar amount of phosgene in the system is maintained at an excess rate of 5 to 20% relative to the total molar amount of the monomer of the structure of formula (I) and the monomer of the structure of formula (II);

[0025] Preferably, the time for introducing phosgene is 30 to 120 min, preferably 60 to 80 min.

[0026] Specifically, the end-capping agent in step 2 is selected from any one of phenol, p-tert-butylphenol, and cumylphenol, or a combination of at least two thereof; preferably, the amount of the end-capping agent added is 1 to 10%, preferably 2 to 5%, of the total molar amount of the monomer of the structure of formula (I) and the monomer of the structure of formula (II).

[0027] Specifically, the alkali solution in step 2 is an aqueous solution of alkali, with a concentration of 5 to 50 wt%, preferably 5 to 32 wt%, wherein the alkali is an inorganic alkali selected from any one of NaOH, KOH, LiOH, and CsOH or a combination of at least two thereof;

[0028] Preferably, the alkali solution is introduced for 30-120 min, preferably 60-80 min.

[0029] In a preferred embodiment, in step 2, the alkali solution and phosgene are introduced into the system simultaneously, using a continuous feeding method, preferably a dropwise method, that is, the alkali solution is continuously added dropwise during the reaction, and the total molar amount of the alkali added in step 2 is maintained at least 300% of the excess phosgene molar amount, preferably 300-600%;

[0030] In a preferred embodiment, in step 2, the polymerization reaction has a reaction temperature of 25 to 37° C., preferably 33 to 35° C., and a reaction time of 30 to 120 min, preferably 60 to 90 min.

[0031] Preferably, a catalyst is further added in step 2 of the present invention, and the catalyst is selected from any one or a combination of at least two of tertiary amines and organophosphorus, preferably triethylamine and / or trimethylamine;

[0032] Preferably, the amount of the catalyst added is 0.1 to 1 mol% of the total molar amount of the monomer of formula (I) and the monomer of formula (II);

[0033] Preferably, the catalyst is added continuously during the reaction, preferably dropwise into the reaction system, and the addition time is 40 to 100 minutes, preferably 60 to 80 minutes;

[0034] More preferably, the catalyst is prepared as a solution with a concentration of 1 to 6 wt% and then added to the system, and the solvent is selected from any one of dichloromethane, chloroform, and toluene, or a combination of at least two thereof.

[0035] In a preferred embodiment, after the polymerization reaction of the present invention is completed, the post-treatment steps such as separation, washing, desolvation, and drying are also included, which are conventional operations in the art. For example, the post-treatment method that can be used is: collecting the oil phase of the reaction liquid, washing with hydrochloric acid and deionized water in sequence until the conductivity does not exceed 100 μs / cm, desolvation, powdering, and drying to obtain the copolycarbonate resin.

[0036] In a second aspect, the present invention provides a copolycarbonate resin having structures represented by formula (III) and formula (IV).

[0037]

[0038] Wherein, R1, R2, R3, and R4 are independently selected from H, halogen, C1-C 10 alkyl (preferably C1-C3 alkyl), C5-C6 cycloalkyl, C6-C 10 Any one of the aromatic groups; R5, R6, and R7 are independently selected from H, C1 to C 10 Any one of an alkyl group (preferably a C1-C3 alkyl group).

[0039] In a preferred embodiment of the present invention, the tensile modulus of the copolycarbonate resin is 2300-2700 MPa, and the flexural modulus is 2400-2850 MPa.

[0040] In a preferred embodiment of the present invention, the weight average molecular weight of the copolycarbonate resin is 10,000 to 100,000, preferably 30,000-35,000.

[0041] In a preferred embodiment of the present invention, the relative dielectric constant of the copolycarbonate resin at 1 MHz is 2.5 to 2.8, preferably 2.5 to 2.7; the relative dielectric constant at 100 Hz is 2.6 to 2.9, preferably 2.6 to 2.8.

[0042] In a third aspect, the present invention provides an application of a copolycarbonate resin.

[0043] An application of a copolycarbonate resin, wherein the copolycarbonate resin is the above-mentioned resin, or is a resin prepared by the above-mentioned method, and the resin is used for blending and modifying with other plastics, preferably blending and modifying with one or more of PC, ABS, PMMA, and PS.

[0044] In one embodiment of the present invention, the resin is used for extrusion granulation to obtain pellets, preferably for processing PC injection molded products, more preferably for injection molding of car lights, aluminum-plated parts, frame parts, face screens, etc.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] The present invention increases the concentration of the monomer formulation liquid corresponding to the structure of formula (I) so that the prepared copolycarbonate has a lower relative dielectric constant, improved tensile modulus and bending modulus, and can also improve the production efficiency of the copolycarbonate. DETAILED DESCRIPTION

[0047] In order to better understand the technical solution of the present invention, the following examples will further illustrate the method provided by the present invention, but the present invention is not limited to the listed examples, and should also include any other known changes within the scope of the claims of the present invention.

[0048] A copolycarbonate resin comprising structural units of formula (I) and formula (II) is prepared according to the phosgene interfacial polycondensation method, wherein the increased production efficiency after the structural monomer of formula (I) is concentrated can be calculated by the formula: increased production efficiency = (C2-C1) / C1×100%, wherein C1: the concentration of the formula liquid of the structural monomer of (I) in the prior art is generally 140g / L-150g / L, and 150g / L is taken for calculation here, and C2: the concentration of the formula liquid of the structural monomer of formula (I) after concentration.

[0049] The present invention is further explained below by more specific examples, but does not constitute any limitation.

[0050] The sources of raw materials used in the following examples and comparative examples are as follows:

[0051] BPTMC, MacLean Biochemical Technology Co., Ltd., purity >99%;

[0052] Bisphenol A (monomer of formula II), Aladdin Reagent Co., Ltd., purity > 98%;

[0053] Bisphenol Z, Aladdin Reagent Co., Ltd., purity >98%;

[0054] 1,1'-Bis(4-hydroxy-3-methylphenyl)cyclohexane, Beijing Bailingwei Technology Co., Ltd., purity>98%;

[0055] Sodium dithionite (deoxidizer), Aladdin Reagent Co., Ltd., purity >98%;

[0056] p-tert-Butylphenol, Aladdin Reagent Co., Ltd., purity >99%;

[0057] Triethylamine, Aladdin Reagent Co., Ltd., purity >98%;

[0058] The prepared copolycarbonate powder was tested for relevant properties using the following methods:

[0059] Weight average molecular weight, determined by size exclusion gel chromatography after pre-calibration with PS or polycarbonate calibration material, instrument manufacturer: Agilent Technologies, column model: PLgel 5μm

[0060] The tensile modulus and flexural modulus are tested by a universal testing machine, referring to ISO527-1 / 2 and ISO178 standards respectively.

[0061] The relative dielectric constant is tested by a dielectric constant tester and is tested in accordance with the IEC60250 standard.

[0062] The phosgene interfacial polycondensation method mentioned in the present invention is a method known in the art and can be synthesized by referring to patent CN115651183B.

[0063] Example 1

[0064] A copolycarbonate resin containing structures of formula (III) and formula (IV) was synthesized in a molar ratio of 20:80.

[0065] Take two 10L reactors with stirring paddles, start stirring, introduce nitrogen protection, and introduce 30°C constant temperature water into the jacket. Reactor 1 is used to prepare the monomer batching liquid of BPTMC, and reactor 2 is used to prepare the monomer batching liquid of BPA. The specific composition is as follows:

[0066] In kettle 1, add 620g (2mol) BPTMC, 500.44g 32wt% NaOH lye, 2714.35g pure water, 1g sodium dithionite, mix well to prepare a BPTMC solution with a concentration of 175g / L and a pH value of 11;

[0067] In kettle 2, add 1824g (8mol) BPA, 1485.68g 32wt% NaOH lye, 9427.73g pure water, and 1g sodium dithionite, mix well to prepare a BPA solution with a concentration of 155g / L and a pH value of 12;

[0068] Take a 20L reactor (kettle 3) for polymerization reaction, start stirring, pass nitrogen protection, and pass 30°C constant temperature water in the jacket, use a peristaltic pump to add the monomer formulation liquid of kettle 1 and kettle 2 to kettle 3, set the dropping speed of the BPTMC monomer formulation liquid to 127.83g / min, the dropping speed of the BPA monomer formulation liquid to 424.61g / min, and the monomer formulation liquid is added dropwise for 30min. At the same time, 22000g of dichloromethane solution (37.9g ​​(0.25mol) of p-tert-butylphenol is dissolved in the solution) is added to kettle 3, and phosgene is continuously passed. The excess rate of phosgene relative to the total molar amount of BPTMC and BPA is 12%, and the speed is controlled to be 24.64g / min for 45min. While passing phosgene, 600g of 32wt% NaOH alkali solution is added dropwise to the reactor, and the dropping speed is controlled to be 13.33g / min for 45min. Then, triethylamine solution (mass fraction of 1%, solvent is dichloromethane) was added dropwise to the reactor at a dropping speed of 16.7 g / min for 60 min. After the reaction was completed, the oil phase was collected and washed with 2 L of 0.4 mol / L hydrochloric acid. After the acid washing was completed, the oil phase was collected and washed with 5 L of deionized water until the conductivity was 100 μs / cm. The washed oil phase was then powdered and dried to obtain a copolycarbonate resin, numbered A1, with a weight average molecular weight of 30123.

[0069] Example 2

[0070] A copolycarbonate resin containing structures of formula (III) and formula (IV) was synthesized in a molar ratio of 50:50.

[0071] Compared with Example 1, the main changes in kettle 1 and kettle 2 are as follows:

[0072] In kettle 1, add 1550g (5mol) BPTMC, 1250.78g 32wt% NaOH lye, 3910.11g pure water, 1g sodium dithionite, mix well to form a BPTMC solution with a concentration of 250g / L and a pH value of 12. During the polymerization reaction, the dropwise addition rate is controlled to be 223.7g / min;

[0073] In kettle 2, 1140 g (5 mol) BPA, 947.52 g 32 wt% NaOH lye, 5624.58 g pure water, and 1 g sodium dithionite were added, and mixed evenly to form a BPA solution with a concentration of 160 / L and a pH value of 12.5. During the polymerization reaction, the dropwise addition rate was controlled to be 257.1 g / min;

[0074] Except for the above changes, the rest is based on Example 1 to synthesize a copolycarbonate resin numbered A2 with a weight average molecular weight of 31232.

[0075] Example 3

[0076] The copolycarbonate powder containing the structures of formula (III) and formula (IV) was synthesized at a molar ratio of 70:30.

[0077] Compared with Example 1, the main changes in kettle 1 and kettle 2 are as follows:

[0078] In kettle 1, add 2170g (7mol) BPTMC, 1837.5g 32wt% NaOH lye, 3569.3g pure water, 1g sodium dithionite, mix well to make a BPTMC solution with a concentration of 310g / L and a pH value of 13, and control the dropwise addition speed to 252.59g / min;

[0079] In kettle 2, add 684g (3mol) BPA, 603.43g 32wt% NaOH lye, 3199.61g pure water, and 1g sodium dithionite, mix well to form a BPA solution with a concentration of 165g / L and a pH value of 13, and control the dropwise addition speed to 149.60g / min;

[0080] Except for the above changes, the rest is based on Example 1 to synthesize a copolycarbonate resin numbered A3 with a weight average molecular weight of 32354.

[0081] Example 4

[0082] The copolycarbonate powder containing the structures of formula (III) and formula (IV) was synthesized with a molar ratio of 90:10.

[0083] Compared with Example 1, the main changes in kettle 1 and kettle 2 are as follows:

[0084] In kettle 1, add 2790g (9mol) BPTMC, 2574.37g 32wt% NaOH lye, 3517.68g pure water, 1g sodium dithionite, mix well to make a BPTMC solution with a concentration of 340g / L and a pH value of 13.5, and control the dropping speed to 296.10g / min;

[0085] In kettle 2, add 228g (1mol) BPA, 216.74g 32wt% NaOH lye, 981.77g pure water, and 1g sodium dithionite, mix well to form a BPA solution with a concentration of 173g / L and a pH value of 13.3, and control the dropwise addition rate to 47.58g / min;

[0086] Except for the above changes, the rest is based on Example 1 to synthesize a copolycarbonate resin with a code number of A4 and a weight average molecular weight of 33329.

[0087] Example 5

[0088] Except that BPTMC was replaced by bisphenol Z (536 g, 2 mol), the rest was the same as in Example 1, the corresponding bisphenol Z formulation liquid concentration was 165 g / L, the dropping speed of the bisphenol Z monomer formulation liquid was set to 125.06 g / min, the monomer formulation liquid dropping time was 30 min, and the rest was the same as in Example 1, to synthesize a copolycarbonate resin numbered A5 with a weight average molecular weight of 29233.

[0089] Example 6

[0090] Except that BPTMC was replaced by 1,1'-bis(4-hydroxy-3-methylphenyl)cyclohexane (593 g, 2 mol), the corresponding 1,1'-bis(4-hydroxy-3-methylphenyl)cyclohexane formulation liquid concentration was 171 g / L, the dropping speed of 1,1'-bis(4-hydroxy-3-methylphenyl)cyclohexane monomer formulation liquid was set to 126.96 g / min, the dropping time of the monomer formulation liquid was 30 min, and the rest was referred to Example 1 to synthesize a copolycarbonate resin numbered A6 with a weight average molecular weight of 32132.

[0091] Comparative Example 1

[0092] A copolycarbonate containing structures of formula (III) and formula (IV) was synthesized with a molar ratio of 20:80.

[0093] Compared with Example 1, the main changes in kettle 1 and kettle 2 are as follows:

[0094] In kettle 1, add 620g (2mol) BPTMC, 500.52g 32wt% NaOH lye, 3353.4g pure water, 1g sodium dithionite, mix well to prepare a BPTMC solution with a concentration of 150g / L and a pH value of 11;

[0095] In kettle 2, add 1824g (8mol) BPA, 1475.94g 32wt% NaOH lye, 10315.91g pure water, and 1g sodium dithionite, mix well to prepare a BPA solution with a concentration of 145g / L and a pH of 11.5;

[0096] The dropping speed of the BPTMC monomer formulation liquid was set to 149.16 g / min, the dropping speed of the BPA monomer formulation liquid was set to 453.9 g / min, the dropping time of the monomer formulation liquid was set to 30 min, and the rest was referred to Example 1 to synthesize a copolycarbonate resin numbered 1 with a weight average molecular weight of 30265.

[0097] Comparative Example 2

[0098] A copolycarbonate containing structures of formula (III) and formula (IV) was synthesized with a molar ratio of 20:80.

[0099] Compared with Example 1, only the composition of kettle 1 was changed, and the concentration of the batching liquid in kettle 2 remained unchanged:

[0100] In kettle 1, add 620g (2mol) BPTMC, 500.52g 32wt% NaOH lye, 3353.4g pure water, 1g sodium dithionite, mix well to prepare a BPTMC solution with a concentration of 150g / L and a pH value of 11;

[0101] The dropping speed of the BPTMC monomer formulation liquid was set to 149.16 g / min, the dropping speed of the BPA monomer formulation liquid was set to 424.61 g / min, the dropping time of the monomer formulation liquid was set to 30 min, and the rest was referred to Example 1 to synthesize a copolycarbonate resin numbered 2 with a weight average molecular weight of 30565.

[0102] The performance test results of the copolycarbonates prepared in the above examples and comparative examples are shown in the following table.

[0103]

[0104]

[0105] It can be seen from the table that increasing the concentration of the formula (I) monomer in the formulation is beneficial to reducing the relative dielectric constant of the resin and improving production efficiency. At the same time, due to the formation of the block structure, it is beneficial to improve the tensile modulus and the flexural modulus.

[0106] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention. Those skilled in the art will appreciate that, under the guidance of this specification, some modifications or adjustments may be made to the present invention. These modifications or adjustments should also be within the scope defined by the claims of the present invention.

Claims

1. A method for preparing a copolycarbonate resin, characterized in that: The following steps are included: A: preparing monomer formulation solutions of formula (I) and formula (II); B: In an inert gas environment, in the presence of an organic solvent and a capping agent, the above monomer formulation liquid, alkali solution, and phosgene are introduced for polymerization reaction to prepare a copolycarbonate resin; wherein, The concentration of the monomer formulation liquid of the control formula (I) structure is 160g / L to 346g / L, preferably 216g / L to 325g / L, more preferably 292g / L to 314g / L, and the pH value of the formulation liquid is 11 to 13.5, preferably 12 to 13.

2. The preparation method according to claim 1, characterized in that: The monomers of the structure of formula (I) and formula (II) are as follows: Among them, R 1 , R 2 , R 3 , R 4 are independently selected from H, halogen, C1-C 10 alkyl (preferably C1-C3 alkyl), C5-C6 cycloalkyl, C6-C 10 The aryl group; R 5 , R 6 , R 7 are independently selected from H, C1-C 10 An alkyl group (preferably a C1-C3 alkyl group).

3. The preparation method according to claim 1 or 2, characterized in that: The monomer of the formula (I) is selected from one or more of BPTMC, bisphenol Z, and 1,1'-bis(4-hydroxy-3-methylphenyl)cyclohexane, and more preferably BPTMC.

4. The preparation method according to any one of claims 1 to 3, characterized in that The concentration of the monomer formulation liquid of the formula (II) is 155 g / L to 175 g / L, preferably 165 g / L to 170 g / L; the pH value of the formulation liquid is 12 to 13.5, preferably 12.5 to 13.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The monomer formulation liquid in step A contains alkali, water, deoxidizer, monomers of formula (I) and / or monomers of formula (II); preferably, in step A, monomers of formula (I) and monomers of formula (II) are formulated separately.

6. The preparation method according to any one of claims 1 to 5, characterized in that: In the polymerization process of step B, the molar ratio of the monomers of formula (I) to formula (II) is 1:99 to 99:1, preferably 10:90 to 70:30, and more preferably 30:70 to 40:

60.

7. The preparation method according to claim 5, characterized in that: In step A, the base in the monomer formulation liquid is an inorganic base, selected from any one of NaOH, KOH, LiOH, CsOH or a combination of at least two thereof; and / or: the deoxidizer is selected from sodium dithionite and / or potassium dithionite, and the added amount of the deoxidizer is preferably 0.1 to 0.3% of the total molar amount of the monomer of formula (I) and the monomer of formula (II).

8. The preparation method according to claim 1, characterized in that: The organic solvent in step B is selected from any one or a combination of at least two of dichloromethane, chloroform, tetrachloromethane, dichloroethane, toluene and chlorobenzene; and / or: The phosgene is added continuously, and the phosgene is continuously introduced during the reaction, and the total molar amount of phosgene in the system is maintained at 5-20% excess relative to the total molar amount of the monomer of the structure of formula (I) and the monomer of the structure of formula (II). The time for introducing phosgene is preferably 30-120 minutes, more preferably 60-80 minutes; and / or: The end-capping agent is selected from any one of phenol, p-tert-butylphenol, and cumylphenol, or a combination of at least two thereof, and the amount of the end-capping agent added is preferably 1 to 10% of the total molar amount of the monomer of the structure of formula (I) and the monomer of the structure of formula (II), more preferably 2 to 5%; and / or: The alkali solution is added continuously to maintain the total molar amount of the alkali in the system of step B to be at least 300%, preferably 300-600% of the molar amount of the excess phosgene; and / or: The alkali solution is an aqueous solution of alkali, with a concentration of 5-50wt%, preferably 5-32wt%, wherein the alkali is an inorganic alkali, selected from any one or a combination of at least two of NaOH, KOH, LiOH, and CsOH, and the introduction time of the alkali solution is preferably 30-120min, more preferably 60-80min; and / or: The polymerization reaction has a reaction temperature of 25 to 37° C., preferably 33 to 35° C., and a reaction time of 30 to 120 min, preferably 60 to 90 min.

9. A copolycarbonate resin prepared by the preparation method according to any one of claims 1 to 8, characterized in that: It has the structure shown in formula (III) and formula (IV): Among them, R 1 , R 2 , R 3 , R 4 are independently selected from H, halogen, C1-C 10 alkyl (preferably C1-C3 alkyl), C5-C6 cycloalkyl, C6-C 10 The aryl group; R 5 , R 6 , R 7 are independently selected from H, C1-C 10 An alkyl group (preferably a C1-C3 alkyl group); Preferably, the tensile modulus of the resin is 2300-2700 MPa, and the flexural modulus is 2400-2850 MPa; preferably, the weight average molecular weight of the resin is 10000-100000, and more preferably, 30000-35000; preferably, the relative dielectric constant of the resin at 1 MHz is 2.5-2.8, and more preferably, 2.5-2.7; and the relative dielectric constant at 100 Hz is 2.6-2.9, and more preferably, 2.6-2.

8.

10. An application of a copolycarbonate resin, wherein the resin is prepared by the preparation method according to any one of claims 1 to 8 or the copolycarbonate resin according to claim 9, characterized in that: The resin is used for blending and modification with one or more of PC, ABS, PMMA and PS, extruded and granulated to obtain pellets, which are used for processing PC injection molded products, preferably for injection molding of headlights, aluminum-plated parts, frame parts and face screens.

Citation Information

Patent Citations

  • Preparation method of polycarbonate

    CN103570931A

  • Preparation method of phosgene method copolycarbonate, copolycarbonate prepared by phosgene method and application of copolycarbonate

    CN115651183A

  • Copolycarbonate powder as well as preparation method and application thereof

    CN117801250A

  • Method for producing polycarbonate

    JP2005008688A